"A Jail within a Jail": Concealment and Unveiling as Narrative Structure in Colson Whitehead's The Nickel Boys. Issue 2 (15th March 2022) - Martín-Salván, Paula
ABSTRACT: This essay analyzes Colson Whitehead's 2019 novel The Nickel Boys through the prism of the tension between concealment and unveiling, and its impact on the text's rhetorical, narrative and ideological structure. The novel focuses on its main character's experience of confinement at Nickel School, a juvenile correction institution. Like most prison narratives, it conceptualizes such experience in terms of an opposition between outside and inside, sliding over the legal and ethical dialectics between freedom and confinement. Thus, a rhetorical structure is articulated in the text around these and other parallel binaries: visible-concealed, public-secret/private. My interpretation of the novel relates these dichotomies to the pattern of confinement and redemption which is typical of the African American prison narrative. Furthermore, in terms of narrative progression, the text is organized as a structure of unveiling, in which the delayed disclosure of key information regarding the main characters forces a reconsideration of the entire sequence of events organized through causal relations. The novel relies on the mechanism of the "surprise ending" in order to solve its structural tensions, provoking not only the reconstruction of its lineal sequence, but a readjustment in the readers' ethical judgment of what has been previously read.